Study of WF Profile Analysis as a Compression Element Reviewed Based on the Weight to Strength Ratio Using the LRFD Method - Kharisma Nur Cahyani; Yehezkiel Septian Yoganata; Rif’atul Khusniah; Kartika Purwitasari (Asosiasi Dosen Muda Indonesia, 2025)
This study investigates the efficiency of WF steel profiles as compression members by evaluating the strength-to-weight ratio using the Load and Resistance Factor Design (LRFD) method. The analysis was conducted on seven variations of WF profiles made of ASTM A36M steel (Fy = 250 MPa, Fu = 450 MPa). The primary parameters considered were axial compressive capacity and profile weight, which were used to determine the strength-to-weight ratio as an indicator of material efficiency. This study contributes to existing research by integrating a systematic strength-to-weight–based evaluation to support optimal WF profile selection beyond conventional strength verification. The results indicate that the strength-to-weight ratio ranges from 592.15 to 611.31, with the highest value obtained for profile 300.300.9.14. In contrast, the maximum compressive capacity of 260,599 kg was achieved by profile 300.300.11.17. Overall, WF profiles with 300×300 dimensions demonstrate superior performance compared to 250×250 profiles in terms of both strength and efficiency. The findings suggest that profile selection may be adapted to design priorities, emphasizing either material efficiency or maximum load-carrying capacity.